AN ANALYSIS ON THE MOBILE PAYMENT INDUSTRY IN CHINA AND ITS IMPLICATIONS TO MALAYSIA - Tong, Wei Lee (PEOPLE: International Journal of Social Sciences, 2020)
Internet which is one of the most transformative and fast-growing technologies has become an integral part of our lives. Globally, the number of Internet users increased from only 413 million in 2000 to over 4.5 billion as of June 2019, with the Internet users from Asia Pacific made up the major market share. Owing to changing lifestyle and rapid growth in E-commerce, this trend is expected to continue over for subsequent many years especially in China. China’s mobile payment transaction volume has reached 190.5 trillion Yuan in 2018, with a year-on-year growth rate of 58.4% due to its advantages of security, stability and convenience. Meanwhile, Malaysia which represents one the fastest growing mobile payment market in the world, has its mobile payment usage skyrocketed in the last five years reaching a staggering 40 billion ringgit. Since 2005, the year when Central Bank of Malaysia liberalized its policy by permitting non-banking institution to provide mobile payment service, there were only 1billion ringgit spent via 365.6 million transactions. 13 years later, the transaction volume has increased to 11 billion ringgit with 1.92 billion transactions made. This implies that there is a huge development opportunity of mobile payment industry in Malaysia and the biggest mobile payment industry in the world, China can be a development model for further growth of this industry in Malaysia. Besides analyzing the current development of the mobile payment industry in China at the beginning of this paper by carrying out life cycle analysis, this paper also studies the influencing factors and challenges of mobile payment in China. Moreover, a comparison of the industry in both China and Malaysia has been drawn out by using PEST analysis. Lastly, the author also proposed the measures and suggestions for enhancement of mobile payment industry in Malaysia.